Pemanfaatan Remitan Ekonomi dan Ketergantungan Migran Kembali Bekerja di Luar Negeri - Suyanto Suyanto (Prodi Antropologi Fakultas Ilmu Budaya Universitas Diponegoro, 2018)
The general objective of this study is to examine the use of economic remittances and constraints in economically productive use and their dependence as workers abroad. This study selected a sample of the Kendal Regency region. Determination of the sample using random sampling techniques and the selection of informants using purposive sampling technique. Data collection uses non-participatory observation, structured interviews, and in-depth interviews. The use of economic remittances to meet daily needs, the cost of education, buy land and build houses, buy secondary goods, and buy productive goods. Their dependence continues to work abroad due to the low access to land and the shifting of the cultivation of agricultural commodities from food (rice) to industrial raw materials (tobacco), the narrow employment opportunities in the area, job opportunities in destination countries, wage rates much higher than in Indonesia, and the use of remittances which tend to be non-productive.